Good Corporate Governance Memoderasi Pengaruh Financial Distress Terhadap Manajemen Laba - Puri, Agung Ridangga; Gayatri, Gayatri (E-Jurnal Akuntansi, 2018)
The profit information that is part of the financial statements is often the target of management to maximize its personal interests. Improvement of corporate management is needed to suppress the fraud committed by the management, one of which is applying the concept of Good Corporate Governance (GCG) within the company. This study aims to obtain empirical evidence about the influence of lfinancial distress on earnings management with Good Corporate Governance (GCG) as a moderator. This research was conducted at the LQ45 company from 2012-2016 and listed on the Indonesia Stock Exchange. The method which is used in this research is Moderated Regression Analysis. The result of research, it is known that financial distress has effect on earnings management. The study also found that GCG is able to moderate the effect of leverage on earnings management. Keywords : earnings management, leverage, good corporate governance